2016
DOI: 10.1039/c5an02434j
|View full text |Cite|
|
Sign up to set email alerts
|

A universal strategy for visual chiral recognition of α-amino acids with l-tartaric acid-capped gold nanoparticles as colorimetric probes

Abstract: The ability to recognize and quantify the chirality of alpha-amino acids constitutes the basis of many critical areas for specific targeting in drug development and metabolite probing. It is still challenging to conveniently distinguish the enantiomer of amino acids largely due to the lack of a universal and simple strategy. In this work, we report a strategy for the visual recognition of α-amino acids. It is based on the chirality of L-tartaric acid-capped gold nanoparticles (L-TA-capped AuNPs, ca. 13 nm in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…NP-based enantiomeric recognition and separation have been widely discussed and studied in the past decade. Studies reported chiral -modified nanomaterials for catalysis [70,71], chiral drug separation [71] and sensing [54,55,56,57,58,59,60,63,68,72,73,74]. In this section, we will focus on the enantiomeric recognition and the fabrication of most commonly used gold and silver materials for chiral NPs.…”
Section: Enantiomeric Recognition By Chiral Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…NP-based enantiomeric recognition and separation have been widely discussed and studied in the past decade. Studies reported chiral -modified nanomaterials for catalysis [70,71], chiral drug separation [71] and sensing [54,55,56,57,58,59,60,63,68,72,73,74]. In this section, we will focus on the enantiomeric recognition and the fabrication of most commonly used gold and silver materials for chiral NPs.…”
Section: Enantiomeric Recognition By Chiral Nanoparticlesmentioning
confidence: 99%
“…At present, this generally involves surface modification using chiral ligands; however, recent advances are making the recognition and separation of enantiomers far simpler. One particular achievement in enantiomeric recognition is colorimetric detection, which uses surface-modified NPs to convert recognition events into color changes observable to the naked eye or a UV-Vis spectrometer [52,53,54,55,56,57,58,59,60,61,62]. This makes it ideal for on-site chiral analysis and provides results instantaneously.…”
Section: Introductionmentioning
confidence: 99%
“…An enantiosensor that can achieve visual discrimination of enantiomers is highly desirable, in which a molecular recognition event is translated into an appreciable color change . Recently, owing to low cost, high sensitivity and simplicity, the metal nanoparticles based colorimetric sensors have been applied to detect carbohydrates , amino acid and proteins in aqueous samples, because targeted analyte can readily induce dispersion/aggregation states of metal nanoparticles and thus the reversible color changes .…”
Section: Introductionmentioning
confidence: 99%
“…The increased development of single-enantiomer pharmaceuticals has enhanced the need for rapid and convenient methods for chiral recognition and determination of enantiomeric excess of chiral compounds. 1 There have been various methods for chiral analysis, such as circular dichroism (CD), 2-4 polarimetry, 5 NMR, 1,6 high performance liquid chromatography (HPLC), [7][8][9] gas chromatography (GC), 10 capillary electrophoresis (CE), [11][12][13][14] mass spectroscopy, 15 uorescence spectrometry, [16][17][18] ultraviolet absorption spectroscopy, [19][20][21][22] UV-visible absorption spectroscopy, [23][24][25] near-infrared spectroscopy, 26 resonance Rayleigh scattering spectroscopy, 27 optically active Raman spectroscopy, 28,29 vibrational circular dichroism spectroscopy, 30,31 ITC, 32,33 colorimetric probes [34][35][36] and so on. Most of them are effective and powerful either in chiral recognition or in determination of enantiomeric excess.…”
Section: Introductionmentioning
confidence: 99%
“…The above methods have some drawbacks such as needing addition of chiral auxiliary for derivatization, [7][8][9][10][15][16][17][18][19][20][21][22][23][24][25][26] requiring tedious sample pretreatment, [34][35][36] using expensive and sophisticated instruments, [2][3][4][6][7][8][9]28,29,32,33 being time-consuming, 6,30,31 less sensitive, [2][3][4] destructive, 15 only for chiral recognition. 32,33 Additionally, they are all wet analysis and can't be used for all types of chiral compounds.…”
Section: Introductionmentioning
confidence: 99%